2016
DOI: 10.1590/0103-9016-2015-0294
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial strains from floodplain soils perform different plant-growth promoting processes and enhance cowpea growth

Abstract: Certain nodulating nitrogen-fixing bacteria in legumes and other nodule endophytes perform different plant-growth promoting processes. The objective of this study was to evaluate 26 bacterial strains isolated from cowpea nodules grown in floodplain soils in the Brazilian savannas, regarding performance of plant-growth promoting processes and ability to enhance cowpea growth. We also identified these strains by 16S rRNA sequencing. The following processes were evaluated: free-living biological nitrogen fixation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…(Armanhi et al, 2018;Cao et al, 2015;Castro et al, 2017;Chou et al, 2007;De Meyer et al, 2015;Hoque et al, 2011;Li et al, 2011;Lu et al, 2017;Sun et al, 2017;Thijs et al, 2014;Whang et al, 2014;Xiao et al, 2017). The other genera isolated have been registered in the literature as endophytic bacteria and plant growth promotors (Chen et al, 2001;Costa et al, 2016;Flores-Félix et al, 2014;Guglielmetti et al, 2013;Guimarães et al, 2012;Jaramillo et al, 2013;Mendis et al, 2018;Souza et al, 2015;Wang et al, 2017;Zhang et al, 2016;Zhao et al, 2017). Although the symbiotic relationships of these communities with siratro may be different from those with native Leguminosae species from each phytophysiognomy (Ribeiro et al, 2017;Santos et al, 2017), even rhizobia can act as PGPR by means of various processes, contributing to the sustainability of the ecosystems (Costa et al, 2016;Marra et al, 2012;Oliveira-Longatti et al, 2014).…”
Section: Groups Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Armanhi et al, 2018;Cao et al, 2015;Castro et al, 2017;Chou et al, 2007;De Meyer et al, 2015;Hoque et al, 2011;Li et al, 2011;Lu et al, 2017;Sun et al, 2017;Thijs et al, 2014;Whang et al, 2014;Xiao et al, 2017). The other genera isolated have been registered in the literature as endophytic bacteria and plant growth promotors (Chen et al, 2001;Costa et al, 2016;Flores-Félix et al, 2014;Guglielmetti et al, 2013;Guimarães et al, 2012;Jaramillo et al, 2013;Mendis et al, 2018;Souza et al, 2015;Wang et al, 2017;Zhang et al, 2016;Zhao et al, 2017). Although the symbiotic relationships of these communities with siratro may be different from those with native Leguminosae species from each phytophysiognomy (Ribeiro et al, 2017;Santos et al, 2017), even rhizobia can act as PGPR by means of various processes, contributing to the sustainability of the ecosystems (Costa et al, 2016;Marra et al, 2012;Oliveira-Longatti et al, 2014).…”
Section: Groups Strainsmentioning
confidence: 99%
“…It is widely reported that the nodules of legumes hold rhizobia together with other endophytic bacteria (Castro et al, 2017;Lima et al, 2009;Velázquez et al, 2017) whose role in symbiosis of legumes is little known. However, they may have positive effects since many of these endophytes had mechanisms for plant growth promotion (Armanhi et al, 2018;Costa et al, 2016;Rangel et al, 2016). It thus becomes necessary to study the application of these organisms in coinoculation studies on plants for revegetation in areas after mining activities.…”
Section: Groups Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reports that B. variegata is not capable of nodulation (Sprent, 2009), in agreement with the results in the present work. It was also verified that, independently form nodulation, there was a positive effect from inoculation over seedling height, dry mass of the aerial portion and roots, total dry mass, IQD and foliar contents of N and C. These effects may be attributed, probably not only to the capacity for biological fixation of N 2 , but also to the production of phytohormones (such as auxins, cytokinins and gibberellins) and solubilization of phosphates and exopolisaccharides by diazotrophic bacteria (Gumiere et al, 2014;Costa et al, 2016;Silva et al, 2016;Porto et al, 2016). As registered for strains of the genus Bradyrhizobium, which increased the production of Inga edulis (Porto et al, 2017), many arboreal species are responsive to inoculation, as also the normative from the Ministry of Agriculture, Livestock and Supply (Brasil, 2011) states, for approximately 23 arboreal legume species which have authorization to be inoculated in the seedling stage.…”
Section: Discusionmentioning
confidence: 82%
“…Basic research work of selection or recommendation of inoculants evidences that inoculation stimulates vegetal growth of various species. Works with cowpea showed results with various strains of symbiotic diazotrophic bacteria, established or native, producing hormones, solubilizing nutrients and increasing the biological fixation of nitrogen and productivity (Guimarães et al, 2012;Costa et al, 2016).…”
Section: Discusionmentioning
confidence: 99%